213k views
2 votes
Solve the system of linear equations by elimination.

x + y = 1

5x + 3y = -3

1 Answer

3 votes

Hello from MrBillDoesMath!

Answer:

x = -3, y = 4

Discussion:

x + y = 1 =>

y = 1 -x

Substitute this y value into the second equation:

5x + 3y = -3 =>

5x + 3(1-x) = -3 => 3(1-x) = 3 -3x

5x + 3 - 3x = -3 => 5x -3x = 2x

2x + 3 = -3 => subtract 3 from both sides

2x = -3 -3 = -6 => divide both dies by 2

x = -6/2 = -3

As x+y = 1, (-3) + y = 1 => y = 1 + 3 = 4

Thank you,

MrB

User Ryan Byrne
by
5.8k points